Ovulation induction in polycystic ovarian syndrome - basics for gynecologist - Yadav, Punita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Polycystic ovarian syndrome (PCOS) is the most common problem related to infertility among women. This review looked into the evidence and options available for ovulation induction. The management protocol and their respective efficacy was looked into during the write up of the review. Weight reduction, along with metformin therapy are the initial and efficient way to regain ovulation among obese female. This should be complemented by use of first line medicine like aromatase inhibitors and selective estrogen receptor modulators. The first line is effective in significant proportion of female to induce ovulation and increase live birth rate. However, for those not responding should initially undergo the use of gonadotropins and ovarian drilling. Finally, controlled ovarian stimulation and in vitro fertilization should be considered as it is an invasive, expensive and there are risks of ovarian hyperstimulation and multiple gestation.